Anti-Inflammatory Effectiveness Test Of Ethanol Extract Of Ara Sungsang Leaf ((Asystasia gangetica) On Male White Mice (Mus musculus )Induced By 1% Carrageenan - Cucu Arum Dwi Cahya; Putri Alvanisia Saragih (Jurnal FARMASIMED (JFM), 2025)
Background: Leaf Ara Sungsang, also known as Asystasia gangetica, is a plant that has been used for a long time to treat different health issues, including inflammation. This plant has compounds called flavonoids and tannins, which are thought to help reduce inflammation by stopping certain chemicals that cause it. Objective: This study looked at how well the ethanol extract from Asystasia gangetica leaves works as an anti-inflammatory treatment in male white mice that had been given 1% carrageenan to induce inflammation. Methods: The study used 25 mice, which were split into five groups. One group received sodium diclofenac at 6.5 mg per kg of body weight as a positive control. Another group got 0.5% Na-CMC as a negative control. The other three groups received different doses of the ethanol extract: 100 mg/kg, 200 mg/kg, and 250 mg/kg. All the mice were given 1% carrageenan to create inflammation. Result: The highest level of inflammation was seen at 6 hours. The strongest anti-inflammatory effect was found in the group that received sodium diclofenac. The groups that received the ethanol extract also showed some anti-inflammatory effects, with the highest dose (250 mg/kg) being the most effective. The Na-CMC group did not show any significant anti-inflammatory effect. The data was analyzed using One Way ANOVA, and there were significant differences in the percentage of inflammation reduction between the different treatment groups (p < 0.05). Conclusion:  Based on the percentage of inhibition, it can be concluded that the ethanol extract of ara sungsang leaves at a dose of 250 mg/kgBB has the best anti-inflammatory effect after sodium diclofenac.